Manifestasi perjuangan dalam pidato Yasser Arafat dari sudut analisis wacana kritis - Hj Azizan, Mohamad Rushdan (2012)
The purpose of this research is to find out how language is used to describe a certain idea or event in a leader’s speech. The description actually contains a process and social practice whether in power, ideology, action and others. In this research, the process or social practice that is to be seen is the element of struggle that is ideologically oriented in Yasser Arafat’s discourse. Therefore, ten of Yasser Arafat's speeches delivered at United Nations (UN) and Non- Aligned Movement (NAM) conferences have been chosen to be analysed. The research methodologies carried out for this particular research are library research and content analysis whereby the framework of three dimensional conception of discourse by Fairclough has been used for analysing the texts. This theory has also been integrated with the method and specific principle in the Arabic Language. The descriptive research analysis is focused on the three dimensions which are textual analysis, discourse practice and social process Textual dimension focuses on the lexical and grammatical analysis. The lexical aspect in the discourse is analysed from the semantic relations whereby the grammatical analysis has been examined from the grammatical mood. Discourse practice, on the other hand, discusses the intertextuality and interdiscursivity aspects while the third dimension explains the dialectical relationship between the social process focused in the research and the other two dimensions. From the analysis of the two dimensions, humanitarian and pro diplomatic oriented ideology could be seen through process dimension or social practice. The two types of ideology have been shown by the relationship of dialectical and lexical aspects, the characteristics of sentences and the practical discourse which have been effectively used by the speaker. This research has proven that the relationship of language and ideology could be seen through the framework of Critical Discourse Analysis.